Regionalidade e tradução em Aventuras de Tom Sawyer, de Monteiro Lobato - Soppelsa, Fernanda Bondam (My University, 2015)
Mark Twain was a prominent realistic author and local colorist, known by his colloquial style of writing. He represents the regional oral modality of the English language in the speech of the characters in the novel The Adventures of Tom Sawyer (Aventuras de Tom Sawyer). This master’s thesis aims at comparatively analyzing parts of the original work by Mark Twain, published in 1876, and the translation made by Monteiro Lobato, from 1934. Using the concepts of regionality from Arendt (2012) and Stüben (2013), the objective of this research is to analyze the cultural characteristics of the original novel and verify how the translator, Lobato, transposes the text to the target language, Brazilian Portuguese. In addition, the translational techniques used by Monteiro Lobato are identified, based on the proposals by Vinay and Dalbernet (1971), Barbosa (1990) and Hurtado Albir (2001). Two languages are never enough alike to be considered representative of the same cultural reality, so it is possible to analyze whether there are losses and gains in translation, as confirmed by Bassnett (2005). Following the ideas systematized by Venuti (1995), this work analyzes to what extend the selected translation is a domestication or keeps the cultural elements from the original novel.
Mark Twain, renomado autor realista e local colorist, é conhecido pelo seu estilo coloquial de escrever. A modalidade oral regional da língua inglesa é representada na fala dos personagens do romance The Adventures of Tom Sawyer (Aventuras de Tom Sawyer). Nesta dissertação, é feita uma análise comparativa entre alguns trechos da obra original de Mark Twain, publicada em 1876, e da tradução feita por Monteiro Lobato, em 1934. A partir dos conceitos de regionalidade apresentados por Arendt (2012) e Stüben (2013), o objetivo desta pesquisa é analisar as especificidades culturais da obra original e verificar de que forma o tradutor, Lobato, as transpõe para o texto da língua-meta, o português brasileiro. Além disso, a partir da análise dos trechos selecionados, são identificadas as técnicas tradutórias utilizadas por Monteiro Lobato, com base nas propostas de Vinay e Dalbernet (1971), Barbosa (1990) e Hurtado Albir (2001). Duas línguas nunca serão suficientemente iguais para serem consideradas representativas de uma mesma realidade cultural, sendo possível analisar se há perdas e ganhos na tradução, como corrobora Bassnett (2005). Nos moldes de Venuti (1995), verifica-se se a tradução é sobretudo domesticadora ou estrangeirizadora.
Keywords: Tradução e interpretação; The adventures of Tom Sawyer (Obra literária); Twain, Mark, 1835-1910 - Crítica e interpretação; Lobato, Monteiro, 1882-1948 - Tradutores; Regionalismo na literatura; Translating and interpreting; The adventures of Tom Sawyer (Literary work); Twain, Mark, 1835-1910 - Criticism and interpretation; Lobato, Monteiro, 1882-1948 - Translators; Regionalism in literature